Helicicultura como explotación alternativa pecuaria - Morales Herrera, Damaris Abigail (2021)
Heliciculture is a topic that sounds more important every day in the agricultural sector, where it is seen as an alternative which will help create new ways of obtaining income for both the state and the workers, who are inclined towards this work. When talking about exploitation, it refers to discovering new ways that contribute to the economic sustainability of the country, since we can see that South American countries are exporters of this type of mollusk, which has proteins and mineral elements that help make it a delicacy in European countries such as Spain and France. Entering into the agricultural sector this idea of helicicultural cultivation will help to have more viability, since it will have the help of the government that has the aim of proposing to the people as an undertaking that encourages the reactivation of the country, since it is necessary to have new Income, the same that have been reduced by the fall in oil, therefore, this project has that objective, to raise knowledge about heliciculture, the same that has not been fully developed due to the lack of knowledge. Knowing about the helicicultural sector will have a great impact on society, since this study will have the essentials to strengthen knowledge, which over time has not had the impact that it should have, where it was known that there are different types of snails edibles such as: Hélix aspersa Máxima, Hélix aspersa Müller, Hélix locorum, Helix pomatia and the three types of production system, Open or extensive system, Closed or intensive system, Mixed system, the same as in the development of the study will be recommended which is the most viable to carry out the present study.